Laser thermal ablation of multidrug-resistant bacteria using functionalized gold nanoparticles - Mocan L (Dove Medical Press, 2017)
Lucian Mocan,1,2 Flaviu A Tabaran,3 Teodora Mocan,2,4 Teodora Pop,5 Ofelia Mosteanu,5 Lucia Agoston-Coldea,6 Cristian T Matea,2 Diana Gonciar,2 Claudiu Zdrehus,1,2 Cornel Iancu1 13rd Department of General Surgery, “Iuliu Hatieganu” University of Medicine and Pharmacy, 2Department of Nanomedicine, “Octavian Fodor” Gastroenterology Institute, 3Department of Pathology, University of Agricultural Sciences and Veterinary Medicine, Faculty of Veterinary Medicine, 4Department of Physiology, 53rd Gastroenterology Department, 6Department of Internal Medicine, “Iuliu Hatieganu” University of Medicine and Pharmacy, Cluj-Napoca, Romania Abstract: The issue of multidrug resistance (MDR) has become an increasing threat to public health. One alternative strategy against MDR bacteria would be to construct therapeutic vectors capable of physically damaging these microorganisms. Gold nanoparticles hold great promise for the development of such therapeutic agents, since the nanoparticles exhibit impressive properties, of which the most important is the ability to convert light into heat. This property has scientific significance since is exploited to develop nano-photothermal vectors to destroy bacteria at a molecular level. The present paper summarizes the latest advancements in the field of nanotargeted laser hyperthermia of MDR bacteria mediated by gold nanoparticles. Keywords: bacteria, photo-thermal ablation, gold nanoparticles, antibiotic resistance